Our experience in the bacteriology of gas gangrene - S. Osorio, Hector (Cirugía del Uruguay, 1971)
Bacteriological studies of 14 cases of gaseous gangrene, with isolation of Clostridium welchii in ten cases, is analyzed, with reference to different aspects of the biology of said germ which are of interest in diagnosis, treatment and prophylaxis of gaseous gangrene.